Do health systems cover the mouth? Comparing dental care coverage for older adults in eight jurisdictions. Issue 9 (September 2020) - Allin, Sara; Farmer, Julie; Quiñonez, Carlos; Peckham, Allie; Marchildon, Gregory; Panteli, Dimitra; Henschke, Cornelia; Fattore, Giovanni; Lamloum, Demetrio; Holden, Alexander C.L.; Rice, Thomas
Highlights: Oral health is a core component of overall health and well-being. Financial protection against the cost of dental care varies across countries. This study compares dental coverage for older adults across eight jurisdictions. Four jurisdictions consider dental care within their statutory health systems. Comparable oral health, dental cost and dental utilization data are limited. Abstract: Oral health is an important component of general health, yet there is limited financial protection for the costs of oral health care in many countries. This study compares public dental care coverage in a selection of jurisdictions: Australia (New South Wales), Canada (Alberta), England, France, Germany, Italy, Sweden, and the United States. Drawing on the WHO Universal Coverage Cube, we compare breadth (who is covered), depth (share of total costs covered), and scope (services covered), with a focus on adults aged 65 and older. We worked with local experts to populate templates to provide detailed and comparable descriptions of dental care coverage in their jurisdictions. Overall most jurisdictions offer public dental coverage for basic services (exams, x-rays, simple fillings) within four general types of coverage models: 1) deep public coverage for a subset of the older adult population based on strict eligibility criteria: Canada (Alberta), Australia (New South Wales) and Italy; 2) universal but shallow coverage of the older adult population: England, France, Sweden; 3) universal, and predominantly deep coverage for older adults: Germany; and 4) shallow coverage available only to some subgroups of older adults in the United States. Due to the limited availability of comparable data within and across jurisdictions, further research would benefit from standardized data collection initiatives for oral health measures.